9.4k views
2 votes
Triangle EFG undergoes a dilation centered at the origin. The result is triangle E'F'G'. Which rule describes the dilation? A) (x, y) → (2x, 2y) B) (x, y) → (4x, 4y) C) (x, y) → (1 4 x, 1 4 y) D) (x, y) → (−4x, −4y)

Triangle EFG undergoes a dilation centered at the origin. The result is triangle E-example-1
User Ed Heal
by
5.7k points

2 Answers

4 votes

Answer:

Answer D I think

Explanation:

User Fuseblown
by
4.9k points
6 votes

Answer:

this was an enlargement

Explanation:

E (0,2) when dilated by 4 is (0,8)

they are all dilated by a scale of 4

User RMX
by
5.9k points